ANALISIS PENYEBAB KESULITAN BELAJAR KOMPUTER AKUNTANSI PADA SISWA KELAS XI AKUNTANSI SMK NURUL FALAH PEKANBARU - Surbakti, Rosmiati; Armas, Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac : This study aimed to determine what factors are the cause of accounting computer learning difficulties in class XI Accounting student of SMK Nurul Falah Pekanbaru. The study lasted from July to December 2015. The population in this study were all students of class XI Accounting SMK Nurul Falah Pekanbaru totaling 58 students. The sampling technique is purposive sampling sample selection based on consideration of the particular destination where consideration is the student who can not do the work according to the schedule at least 3 times totaling 35 students. Data collection instruments used were questionnaires were processed using semantic differential scale with variable depender: learning difficulties (Y); independent variables: internal factors (X1) and external factors (X2). From the results it can be concluded that based on the results of descriptive analysis 89.98% of the students agreed to external factors and 73.16% agree to internal factors so that external factors more influential in causing learning difficulties accounting computer in class XI student of SMK Nurul Falah Accounting Pekanbaru. The same is indicated by the results of the t test where t test result of external factors 2.907> 2.78 t internal factors.Key words : factors, causes, learning difficulties, computer accounting